2004
DOI: 10.1109/tnn.2004.824262
|View full text |Cite
|
Sign up to set email alerts
|

Scalar Equations for Synchronous Boolean Networks With Biological Applications

Abstract: One way of coping with the complexity of biological systems is to use the simplest possible models which are able to reproduce at least some nontrivial features of reality. Although two value Boolean models have a long history in technology, it is perhaps a little bit surprising that they can also represent important features of living organizms. In this paper, the scalar equation approach to Boolean network models is further developed and then applied to two interesting biological models. In particular, a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 13 publications
0
69
1
Order By: Relevance
“…In general, a synchronous Boolean network contains n nodes (x 1 , x 2 , x 3 …, x n ), with each node updating itself with each other in a synchronous manner (Milligan and Wilson, 1993;Farrow et al, 2004). Each node has only 1 Boolean value: 1 (ON) or 0 (OFF) at 1 moment.…”
Section: Synchronous Boolean Network and Basic Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a synchronous Boolean network contains n nodes (x 1 , x 2 , x 3 …, x n ), with each node updating itself with each other in a synchronous manner (Milligan and Wilson, 1993;Farrow et al, 2004). Each node has only 1 Boolean value: 1 (ON) or 0 (OFF) at 1 moment.…”
Section: Synchronous Boolean Network and Basic Definitionsmentioning
confidence: 99%
“…For the same GRNs, different modeling methods can be used, such as synchronous (Farrow et al, 2004;Fauré et al, 2006;Remy et al, 2006), asynchronous (Fauré et al, 2006;Garg et al, 2008) and semi-asynchronous (Fauré et al, 2006) models. Dubrova et al (2005) presented a basic algorithm known as BooleNet to identify attractors in synchronous Boolean networks.…”
Section: Introductionmentioning
confidence: 99%
“…An SBN is a set of n nodes (node 1 , node 2 , node 3 ,..., node n ) which interact with each other in a synchronous manner (Farrow et al, 2004). At each given time t ∈ N each node has only one of two different values: 1 (ON) or 0 (OFF).…”
Section: Three Classes Of Scas For Sbnsmentioning
confidence: 99%
“…Recently, Heidel (Heidel et al, 2003) and Farrow (Farrow et al, 2004) found the SCAs in synchronous Boolean networks. Zhao (Zhao, 2005) also proved the computing SCAs' methods in synchronous Boolean networks to be a nondeterministic polynomial time (NP) complete problem.…”
Section: Introductionmentioning
confidence: 99%
“…The Boolean network, first introduced by Kauffman (Kauffman, 1969), has been proved to be quite useful in modeling and quantitative description of cell regulation (Kauffman, 1969;Huang and Ingber, 2000;Huang, 2002;Farrow et al, 2004).…”
Section: Introductionmentioning
confidence: 99%